An annotated checklist of the family Diaptomidae Sars, 1903 (Copepoda, Calanoida) in Vietnam - Luong, Tran Duc; Hai, Ho Thanh; Thanh, Dang Ngoc (Academia Journal of Biology, 2016)
This paper is based litenature reviews and on our own data from voucher specimens deposited in the Institute of Ecology and Biological Resources (IEBR), Vietnam. The taxonomic status of species within Diaptomidae Sars, 1903 in Vietnam has recently been revised. A total of thirteen genera and twenty-nine species have been recorded and a comprehensive catalogue including the illustrates and distribution of all species of the Diaptomidae in Vietnam has been presented here. Among them, eight endemic species were listed; seven species have been changes in the nomenclature and the classification’s position and eight species updated on the the latest list of Diaptomidae of Dang & Ho, 2001a